MANAJEMEN SUMBER DAYA MANUSIA DI PONDOK MODERN DARUSSALAM GONTOR KAMPUS 12 - Tri Wahyuni; Shabrina Alsha Putri Almatasya; Zia Shakila (STKIP Pesisir Selatan, 2026)
This study aims to explore the implementation of human resource management (HRM) at Pondok Modern Darussalam Gontor Campus 12, focusing on workforce planning, recruitment and selection, training and development, performance appraisal, and the reward system for educators and educational staff. A descriptive qualitative approach was used to gain an in-depth understanding of HRM practices based on values of sincerity, dedication, and moral responsibility in accordance with the pesantren’s philosophy. Data were collected through in-depth interviews, participatory observation, and document analysis, then analyzed using content and thematic analysis techniques. The findings show that Gontor Campus 12 applies a non-formal HRM system that emphasizes direct observation and collective deliberation rather than numeric-based evaluation. Rewards are given in the form of trust and responsibility, which strengthen the intrinsic motivation of educators. This system effectively builds a work culture grounded in spiritual values and dedication, although it requires a high level of maturity and honesty from the entire pesantren community. These findings are expected to serve as a reference for managers of Islamic educational institutions in integrating professional and spiritual aspects in human resource management.